Analysis of uncertainties associated with different factors used to determine the age of sediments with the Optically Stimulated Luminescence method - Tsodoulos, I. M.; Stamoulis, K.; Papachristodoulou, C. A.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2019)
In this work, a sediment sample from an excavated paleoseismological trench was collected and dated following the Optically Stimulated Luminescence (OSL) dating method, using the Riso TL/OSL DA-20 reader. Chemically purified quartz, from the sample, was analysed following a single-aliquot regenerative-dose (SAR) protocol for the equivalent dose (De) determination. Also, to estimate dose rates, the natural radioactivity of soil from the surroundings of the original sample location was measured, using gamma spectrometry. Since the application of the OSL dating method involves a number of intermediary factors and processes, all being the sources of uncertainties propagating to the total uncertainty, an exhaustive analysis of the involved uncertainties is presented and the implications to the derivation of the final ages are discussed.